Identifying and Prioritizing the Effective Factors in Improving the Performance of Ilam Fire and Safety Services Organization - et. al., Bahram Havasi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of present study was to identify and prioritize the effective factors in improving the performance of Ilam Fire and Safety Services Organization. The study was conducted using qualitative-quantitative method. First, 10 firefighters were interviewed and their opinions were coded and categorized. Then, 12 categories of the factors affecting improvement of the Fire and Safety Services Organization performance in Ilam city were extracted. These factors were extracted through a questionnaire that was distributed among the second statistical population of the study consisting of 83 operational staff and some retirees of the Ilam Fire and Safety Services Organization to confirm or reject accuracy of the factors. One-sample t-test was used to confirm the factors and Friedman test was used to rank them. After comparing the means of each of the proposed factors with the mean “3”, results showed that there was a significant difference between the means and according to Friedman test, the highest mean rank (9.34) was related to wages and welfare facilities and the lowest mean rank (4.55) was related to commanding and operation management.